Service Quality and Patient Trust on Patient Loyalty Mediated by Patient Satisfaction on Inpatients - Andreano, Pillipus Resar; Pardede, Ratlan (International Journal Labs, 2023)
Background: The competition in the health industry is currently very fierce, coupled with the emergence of Private Hospitals equipped with complete facilities. This makes hospitals must realize the need to provide quality health services to their customers. Aim: The purpose of this study was to investigate the effect of service quality and patient trust on patient loyalty mediated by patient satisfaction in patients who hospitalized at “CDE” Hospital, Bogor, West Java. Method: A Google Forms online survey on inpatients at